The Influence of Jodipan Color Utilization as a Learning Source of Ability to Solve Problems in The Theme of Enviromental Pollution - Latifatul Fauzi; Ketut Prasetyo; Mohammad Ali Haidar (IAIN Madura, 2021)
The ability to solve problems is a process in which a person identifies a situation, formulates a hypothesis, verifies a hypothesis made by digging up data, and restarts the hypothesis made to become a generalization (Purwanto, 1999). The focus of this research is to analyze the influence of the use of the Kampung Warna Warni Jodipan as a source of learning for students' ability to solve problems in MTs Attaraqqie Malang on the theme of tackling environmental pollution. This study uses an experimental research design in the form of a Quasi-Experimental Design with the type of pretest posttest control group design. The sample in this study were students of class IX A and IX D with purposive sampling technique. Data collection techniques using test questions in the form of problem description. The data analysis technique in this study was to use the independent sample t-test. The results of this study indicate that there is a significant influence on the use of the Kampung Warna Warni Jodipan as a source of learning for students' problem solving abilities, this is evidenced by the results of the independent sample t-test which shows that there is a significant influence on the use of the Kampung Warna Warni Jodipan. , with tcount> ttable which is 5,450> 2,000. This shows that there are significant differences in the ability to solve problems in the experimental and control classes.